Clinical effectiveness of contrast medium injection protocols for 80-kV coronary and craniocervical CT angiography—a prospective multicenter observational study - Wang, Yining; Chen, Yu; Liu, Peijun; Lv, Wan; Wu, Jianlin; Wei, Mengqi; Shi, Dapeng; Wu, Xianheng; Liu, Wenya; Tao, Xiaofeng; Hu, Hongjie; Ma, Xiangxing; et al. (European radiology, 2022)
Background and objective Decreasing X-ray tube voltage is an effective way to reduce radiation and contrast dose, especially in non-obese patients. The current study focuses on CTA in non-obese patients to evaluate image quality and feasibility of 80-kV acquisition protocols with varying iodine delivery rates (IDR) and contrast concentrations in routine clinical practice. Methods A prospective observational study in patients ≥ 18 years and ≤ 90 kg referred for coronary or craniocervical CTA at 10 centers in China (ClinicalTrials.gov: NCT02840903). Patients were divided into four groups: a standard 100-kV protocol (370 mgI/ml, IDR 1.48 gI/s), and three 80-kV protocols (370 mgI/ml, IDR 1.2 gI/s; 300 mgI/ml, IDR 1.2 gI/s; 300 mgI/ml, IDR 0.96gI/s). The primary outcome was contrast opacification of target vascular segments. Secondary outcomes were image quality (contrast-to-noise ratio, signal-to-noise ratio, visual image quality, and diagnostic confidence assessment), radiation, and iodine dose. Results From July 2016 to July 2017, 1213 patients were enrolled: 614 coronary and 599 craniocervical CTA. The mean contrast opacification was ≥ 300 HU for 80-kV 1.2 gI/s IDR scanned segments; IDR 0.96 gI/s led to lower opacification. Image quality and diagnostic confidence were fair to excellent (≥ 98% of images), despite lower contrast-to-noise ratios and signal-to-noise ratios in 80-kV images. Compared to the standard protocol, 80-kV protocols led to 44–52% radiation dose reductions ( p < 0.001) and 19% iodine dose reductions ( p < 0.001). Conclusion Eighty-kilovolt 1.2 gI/s IDR protocols can be recommended for coronary and craniocervical CTA in non-obese patients, reducing radiation and iodine dose without compromising image quality. Key Points • Using low-voltage scanning CTA protocols, in which tube voltage and iodine delivery rate are reduced proportionally (voltage: 80 kV, IDR: 1.2 gI/s), reduces radiation and contrast dose without compromising image quality in routine clinical practice . • Reducing iodine delivery rate beyond direct proportionality to tube voltage is not beneficial .